PENGARUH E-SERVICE QUALITY DAN PERCEIVED EASE OF USE TERHADAP KEPUASAN PELANGGAN SHOPEE DI KECAMATAN PONDOK MELATI - Amin Sadiqin (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to analyze the effect of e-services quality and perceived ease of use on Shopee customer satisfaction in Pondok Melati District. The research was conducted using quantitative descriptive methods. In this study using the Lemeshow formula, with a sampling error of 10% obtained a sample number of 100 respondents. The data used in this study were primary data collected through questionnaires. Data analysis using SPSS software version 26. The results of the study showed that: 1) E-services quality (X1) had a positive and significant effect on customer satisfaction (Y) on the Shopee application in Pondok Melati District; 2) Perceived ease of use (X2) had a positive and significant effect on customer satisfaction (Y) on the Shopee application in Pondok Melati District; 3) E-services quality (X1) and Perceived ease of use (X2) together have a positive and significant effect on customer satisfaction (Y) on the Shopee application in Pondok Melati District; and 4) The magnitude of the influence of E-services quality (X1) and Perceived ease of use (X2) on customer satisfaction (Y) on the Shopee application in Pondok Melati District was 35.4%, while the remaining 64.6% was influenced by other variables that were not studied in this study